SAT0167 Clinical and Ultrasonographic Evaluation in A Cohort of Sustained Remission Rheumatoid Arthritis Patients after Stopping Biologic Therapy: A Single Center Experience. (10th June 2014) - Batticciotto, A.; Antivalle, M.; Ditto, M.C.; Varisco, V.; Rigamonti, F.; Talotta, R.; Battellino, M.; Ventura, D.; Atzeni, F.; Sarzi-Puttini, P.
Abstract : Background: Rheumatoid arthritis (RA) patients in clinical remission according to the 2011 ACR/EULAR criteria [1] can develop radiographically revealed hand and foot erosions and joint damage when observed 2-5 years later. Some authors have suggested that ultrasound or MRI should be included in the remission criteria in order to assess disease activity more precisely [2]. Ultrasonography (US) is a useful means of diagnosing and following up patients with RA, and power Doppler (PD) technology can evaluate intra- and peri-articular soft tissue inflammation [3]. Objectives: The aim of this prospective study was to evaluate a cohort of patients with RA in sustained remission after stopping biological agents on the basis of clinical and US data. Methods: From among the 302 RA patients receiving biological DMARD therapy attending our centre between January 2011 and December 2012, we selected those satisfying the 2011 ACR/EULAR remission criteria (SDAI <3.3 for more than six months) without glucocorticoid therapy and without any PD signal upon metacarpal phalangeal (MCP) US assessment. After stopping biological DMARDs, they underwent clinical and ultrasonographic examinations every two months or in the case of a disease flare. Biological DMARDs were resumed in the patients with an SDAI score of >11.0 and PDUS positivity in at least one MCP joint. Results: After one year of follow-up, three (23%) of the 13 patients in sustained remission (3 males, 10 females; mean age 59 years, range 24-78; mean disease duration 8.6 years, range 1-30; 61% rheumatoid factor (RF) positive, 58% anti-cyclic citrullinated peptide antibody (anti-CCP) positive; mean biological DMARD treatment duration 39.3 months, range 12-98; 84% concomitantly treated with methotrexate) experienced a disease flare (mean SDAI 19.7; PDUS positive) and resumed biological DMARD therapy after a mean of 5.3 months. One patient (7%) was PDUS positive, but remained in SDAI remission. Three patients (23%) showed a low level of disease activity without PDUS positivity, and six patients (38.4%) remained in clinical and US remission. Intra-class correlation analysis showed a moderate agreement between SDAI and PDUS (ICC=0.67; p=0.034) Conclusions: During the course of a one year follow-up, 23% of a cohort of RA patients in sustained remission (selected by combining US and the 2011 ACR/EULAR remission criteria) experienced a disease flare and needed to resume taking biological DMARDs. References: Y. Tanaka et, al. Discontinuation of biologics in patients with rheumatoid arthritis. Clin Exp Rheumatol 2013; 31 (Suppl. 78): S22-S27. DT. Felson, et al. American College of Rheumatology/European League Against Rheumatism Provisional Definition of Remission in Rheumatoid Arthritis for Clinical Trials. Artritis Rheum 2011;63: 573–86 A. Iagnocco, et al. Ultrasound imaging for the rheumatologist. XVII. Role of colour Doppler and power Doppler. Clin Exp Rheumatol 2008; 26: 759-62. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4003